ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN MATERI PENJUMLAHAN DAN PENGURANGAN MATA PELAJARAN MATEMATIKA - Corry Restuina; Andri Anugrahana; Elisabeth Desiana Mayasari (JURNAL CURERE, 2022)
The purpose of the research is to determine the process of implementing mathematics learning by using Kumon method and to find out the difficulties of the students in completing addition and subtraction material in mathematics subject at level A. This research used a qualitative descriptive research method. This research involved 1 supervisor at the Kumon Setia Budi Center tutoring in Medan and 5 students that studying at Kumon Setia Budi Center tutoring who were at level A.The results of the research are as follows: 1. The learning process of level A mathematics subject at Kumon is 1) Initial activities: greeting, checking homework, giving grades: 2) Core activities: guiding homework, students working on worksheets, guiding working on worksheets: 3). Final activity: giving evaluation, giving homework. 2 The difficulties that faced by the students in completing the addition and subtraction material of mathematics subjects at level A are the students have difficulty using the concept, students have difficulty in completing the addition material, and students have difficulty in adding the two numbers are presented randomly.